Synthesis, Antiinflammatory and Antibacterial Activities of Substituted Phenyl Benzimidazoles - LEONARD, J.T.; RAJESH, O.S.; JEYASEELI, L.; MURUGESH, K.; SIVAKUMAR, R.; GUNASEKARAN, V. (Asian Journal of Chemistry, 2010)
A new series of substituted benzimidazoles as 1-(substituted methy])-2-substituted phenyl) benzimidazoles were synthesized and characterized. The compounds were evaluated for antiinflammatory and antibacterial activity. All the compounds exhibited significant to moderate antiinflammatory and antibacterial activities.